PEMILIHAN ALTERNATIF PERBAIKAN KINERJA LINGKUNGAN PRODUK LAMPU BERBASIS SIMAPRO-5 DENGAN METODA LIFE CYCLE ASSESSMENT (LCA) DAN ANALYTICAL HIERARCHY PROCES (AHP) - Udisubakti Ciptomulyono; Dewi Hajar (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2007)
Life Cycle Management (LCM) is a framework of concepts, techniques and procedures concerned to an environmental management of products and organizations in achieving continuous environmental improvement viewed from life cycle perspective. One tool in LCM approach is Life Cycle Assessment (LCA) which consists of a method to quantify environmental impacts associated to products or activities throughout their life cycle, begins with extraction of raw materials, proceeds through production and use, ends to waste treatment (from cradle to grave). This research deals with analysis of LCA for products of Fluorescent Lamp of 20 Watt. The research question exposed is how to evaluate the best alternative to improve environmental performance among many strategies designed on LCA results. Due to in the real system, environmental consideration is not the only one criteria used for decision making, this research proposes to takes into account for multi criteria evaluation in selection of the best strategy such as criteria of investment cost, corporate image etc, to do so the method of AHP (Analytical Hierarchy Process) is proposed to apply. In order to evaluate the environmental impact associated the process throughout the life cycle the product, existing database built in SimaPro-5 software. This research concludes that the strategy of “product take back” principle is the best solution in order to achieve the optimal environmental performance.